Epidemiology, Risk Factors and Seasonal Variation of Scrub Typhus Fever in Central Nepal - Rajendra Gautam; Keshab Parajuli; Jeevan Bahadur Sherchand (Tropical Medicine and Infectious Disease, 2019)
Scrub typhus is a mite-borne acute febrile illness caused by Orientia. tsutsugamushi, a zoonotic bacterial infection common in the region known as the tsutsugamushi triangle. This study aims to determine the seroprevalence, seasonal variation, and risk factors of scrub typhus among the acute febrile illness patients attending different hospitals of central Nepal. Blood samples were collected from hospitalized patients of acute febrile illness suspected of scrub typhus infection attending different hospitals of central Nepal from April 2017 to March 2018. The IgM antibody to Orientia tsutsugamushi was detected by using the Scrub Typhus Detect™ Kit. Among the total cases (1585), 358 (22.58%) were positive for IgM Antibodies. Multivariate analysis identified several risks factors to be significantly associated with the scrub typhus infection, including gender (female) (odds ratio [OR] = 1.976, p ≤ 0.001, confidence interval [CI] = 1.417⁻2.756), rural residential location (odds ratio [OR] = 0.431, p = 0.001, confidence interval [CI] = 0.260⁻0.715), house near grassland (odds ratio [OR] = 3.288, p ≤ 0.001, confidence interval [CI] = 1.935⁻5.587), and working in the field (odds ratio [OR] = 9.764, p = 0.004, confidence interval [CI] = 2.059⁻46.315). The study findings indicate scrub typhus infection to be a significant health problem in Nepal. The proper diagnosis of infection cases, timely institution of therapy, public awareness, and vector control are important measures to be taken for the prevention and management of scrub typhus.